In Silico Study of Soursop Leaf Compounds (Annona muricata L.) As Inhibitors of BRAF V600E Kinase in Melanoma Cancer - Dewayani, Audry Rahma; Ghaliya, Salsabil; Parameswari, Natashya; Pribadi, Alya Puteri Agustina; Ahadi, Husna Muharram; Aulifa, Diah Lia; Elaine, Angela Alysia; Sitinjak, Bernap Dwi Putra (Jurnal Farmasi Udayana, 2023)
Melanoma is a cancer that develops in melanocytes and manifests itself on the skin as lumps and uneven skin pigmentation. A chemotherapeutic medication called Vemurafenib is one of the medicines used to treat this malignancy. Chemotherapeutic drugs, on the other hand, are known to induce a variety of adverse effects in the body, thus alternative substances with the same potential but fewer side effects must be sought. This study was conducted utilizing an in silico technique, which included molecular docking, as well as Lipinski rules and PreADMET to predict the pharmacokinetic profile. Compounds found in soursop leaves (Annona muricata L.) have been shown to inhibit cell division by interacting with the BRAF V600E receptor. Reticuline has a Gibbs energy of -8.78; a 395.39 nM inhibition constant; and binds to the amino acids GLN A:530, CYS A: 532, and ASP A: 594.